A copper complex formed with neurokinin B: binding stoichiometry, redox properties, self-assembly and cytotoxicity. Issue 11 (21st October 2020) - Huang, Yaliang; Xia, Ning; Chen, Miao; Yang, Ping; Liu, Lin; Wang, Jianxiu
Abstract : This work reveals the binding stoichiometry, redox properties, self-assembly and cytotoxicity of the copper complex formed with neurokinin B. Abstract : The tachykinin neuropeptide of neurokinin B (NKB) is a copper-binding amyloid peptide with important roles in the regulation of physiological functions and pathophysiological processes in the central and peripheral nervous systems. In this work, the formation of a NKB–Cu 2+ complex in a 1 : 1 stoichiometry was confirmed by mass spectrometry. The self-assembly of NKB and its mutant species was investigated by Thioflavin T (ThT) fluorescence assay and atomic force microscopy (AFM), and at the same time, the effect of Cu 2+ on the aggregation of NKB was studied. As evidenced by cyclic voltammetry, the redox potential of NKB–Cu 2+ was determined to be 0.77 V ( vs. Ag/AgCl). It has been demonstrated that NKB at low concentrations exerts its neuroprotective function by inhibiting Cu 2+ -mediated reactive oxygen species (ROS) production in the presence of ascorbic acid (AA). In comparison with equivalent Cu 2+, the peptide–Cu 2+ aggregates aggravated the viability of PC-12 cells more seriously in the absence of AA. These results should be extremely valuable for understanding the NKB/Cu 2+ interactions and the toxicity mechanism of Cu 2+ associated with neurodegenerative diseases.